Early melt season velocity fields of Langjökull and Hofsjökull, central Iceland. Issue 226 (2015) - Minchew, Brent; Simons, Mark; Hensley, Scott; Björnsson, Helgi; Pálsson, Finnur
Abstract: We infer the horizontal velocity fields of the ice caps Langjökull and Hofsjökull, central Iceland, using repeat-pass interferometric synthetic aperture radar (InSAR). NASA's uninhabited aerial vehicle synthetic aperture radar (UAVSAR) acquired airborne InSAR data from multiple vantage points during the early melt season in June 2012. We develop a Bayesian approach for inferring three-dimensional velocity fields from multiple InSAR acquisitions. The horizontal components generally agree with available GPS measurements wherever ice motion is well constrained by InSAR observations. We provide evidence that changes in volumetric moisture content near the glacier surface induce phase offsets that obfuscate the vertical component of the surface velocity fields, an effect that could manifest itself on any glacier that experiences surface melt. Spatial patterns in the InSAR-derived horizontal speeds are broadly consistent with the results of a simple viscous flow model, and the directionality of the InSAR-derived horizontal flow field is nearly everywhere consistent with the ice surface gradient. Significant differences between the InSAR-derived horizontal speed and the speed predicted by the viscous flow model suggest that basal slip accounts for more than half the observed outlet glacier flow.